Identification of Pathways and Key Genes in Venous Remodeling After Arteriovenous Fistula by Bioinformatics Analysis - Jie, Kong; Feng, Wang; Boxiang, Zhao; Maofeng, Gong; Jianbin, Zhang; Zhaoxuan, Lu; Yangyi, Zhou; Liang, Chen; Haobo, Su; Wensheng, Lou; Guoping, Chen; Jianping, Gu; et al. (Frontiers in Physiology, 2020)
The arteriovenous fistula (AVF) is the first choice of vascular access for the hemodialysis of renal failure patients. Venous remodeling after exposing to high fistula flow is important for AVF mature but the mechanism under remodeling is still unknown. The objective of this study is to identify the molecular mechanisms that contribute to the venous remodeling after AVF. To screen and identify the differentially expressed genes (DEGs) that may involve venous remodeling after AVF, we used bioinformatics to download the public microarray data (GSE39488) from the Gene Expression Omnibus (GEO) and screen for DEGs. We then performed Gene Ontology (GO) function analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and Gene set enrichment analysis (GSEA) analysis for functional annotation of DEGs. The protein‑protein interaction (PPI) network was constructed and the hub genes were carried out. Finally, we harvested 12 normal vein samples and 12 AVF vein samples which were used to confirm the expressions of hub genes by immunohistochemistry. 45 DEGs were detected, including 32 upregulated and 13 downregulated DEGs. The biological process (BP) of the GO analysis were enriched in extrinsic apoptotic signaling pathway, cGMP-mediated pathway signaling and molting cycle. The KEGG pathway analysis showed that the upregulated DEGs were enriched in Glycosaminoglycan biosynthesis and Purine metabolism, while the downregulated DEGs were mainly enriched in pathways of Glycosaminoglycan biosynthesis, Antifolate resistance and ABC transporters. The GSEA analysis result showed that the top three involved pathways were the oxidative phosphorylation, the TNFA signaling via NF-ΚB and the inflammatory response. The PPI was constructed and the hub genes founding through the method of DMNC showed that the INHBA and NR4A2 might play an important role in venous remodeling after AVF. The integrated optical density (DOI) examined by immunohistochemistry staining showed that the expression of both the INHBA and the NR4A2 increased in AVF compared to the control group. Our research contribute to the understanding of the molecular mechanism of venous remodeling after exposing to high fistula flow, which may be useful in treating AVF failure.